Determine the Accuracy & Use of Ultrasound Guidance and Alvarado Score for Diagnosing Acute Appendicitis - Nadia Khattak, Syed Imran Haider, Nadeem Akram Butt, Yasrab, Sana Sharif, Asma Afzal Kiani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Appendicitis is one of the most common and frequently encountered operations in surgical emergencies. It is the most frequent cause of acute abdominal pain. Early and accurate diagnosis can reduce the rate of negative appendectomy (surgical removal of appendix) and helps to provide better treatment with no extra cost and complications. Aim: The objective of this study was to examine the accuracy and use of ultrasonography and Alvarado score system for diagnosing Acute Appendicitis. Place and Duration of Study: Radiology Department Hayatabad Medical Complex, Peshawarfor duration of six months from January 2021 to June 2021. Methods: In this cross-sectional observational study, 130 patients of abdominal pain having ages of 10 years to 70 years were included. All patients had diagnosis with Alvarado scoring system and ultrasound for identifying Acute Appendicitis. Patients’ detailed history including age, sex and histopathology and ultrasonographic results were recorded. All statistically data was analyzed by SPSS version 17. P-value <0.05 was considered as significant. Results: Out of 130 patients, 95 (73.08%) patients were men and 35 (26.92%) patients were women. 15 (11.54%) patients were ages less than 20 years, 75 (57.70%) patients having ages between 20 to 39 years, 32 (24.62%) patients were aged between 40 to 59 years and 8 (6.15%) patients were ages of >59 years. Symptoms observed in all patients such as anorexia, nausea and vomiting, tenderness in right iliac fossa, rebound tenderness, elevated temperature as 71.54%, 53.85%, 100%, 95.39% and 84.62% respectively. In all 130 patients 122 (93.85%) had found acute appendicitis by using ultrasound. As per histopathology results 95 % had acute appendicitis and 5 % had chronic or normal appendicitis. Conclusion: It is concluded that Alvarado Score system along with noninvasive ultrasound guidance resulted accurately and helps to reduce the rate of negative appendectomy, complications and infections with no extra cost. The combine role of Alvarado score and ultrasonography can helps to provide better treatment in acute appendicitis.